From Theory to Practice: Leveraging Appreciative Inquiry for Workplace Belonging and Collaboration - Thanetsunthorn, Namporn (Journal of Knowledge Management Practice, 2025)
This study employs the Appreciative Inquiry (AI) framework, a well-established organizational development intervention, as a transformative approach for fostering workplace belonging and employee collaboration within organizations. In essence, AI is grounded in a strengths-based approach, focusing on positive organizational transformation through collaboration. Drawing on the AI theoretical framework and its application, this study proposes a series of reflective questions for each phase of the AI 4-D cycle – Discovery, Dream, Design, and Destiny. These questions are designed to stimulate reflection, encourage meaningful dialogue, and promote active engagement among organizational members. By focusing on organizations’ strengths and successes, these reflective questions help guide organizations in evaluating current diversity, equity, and inclusion (DEI) practices, envisioning a shared future, and developing actionable strategies and initiatives that cultivate a culture of belonging and collaboration. This study discusses both the theoretical and practical implications of using AI to foster sustainable and inclusive organizational environments.
Keywords: knowledge management; appreciative inquiry; strengths-based approach; AI 4-D cycle; positive organizational change; workplace belonging; collaboration